Tailoring modulation instabilities and four-wave mixing in dispersion-managed composite liquid-core fibers - Junaid, Saher; Schaarschmidt, Kay; Chemnitz, Mario; Chambonneau, Maxime; Nolte, Stefan; Schmidt, Markus A. (Optics Express, 2020)
We show that the ultrafast nonlinear dynamics in supercontinuum generation can be tailored via mixture-based liquid core fibers. Samples containing mixtures of inorganic solvents allow changing dispersion from anomalous to normal, i.e., shifting zero dispersion across pump laser wavelength. A significant control over modulation instability and four-wave mixing has been demonstrated experimentally in record-long (up to 60 cm) samples in agreement with simulations when using sub-psec pulses at 1.555 µm. The smallest concentration ratio yields indications of soliton-fission based supercontinuum generation at soliton numbers that are beyond the coherence limit. The presented dispersion tuning scheme allows creating unprecedented dispersion landscapes for accessing unexplored nonlinear phenomena and selected laser sources.
CRIS-Team Scopus Importer:2023-04-20